What does Travel Vlog Mean for Snow Leopard Conservation? - RIGZIN, PADMA (Snow Leopard Reports, 2025)
This article invites snow leopard stakeholders (especially academics and conservation managers) to ponder the long-term conservation implications of snow leopard’s representation in mass-circulated travel vlogs in the context of global environmental changes. By analysing three YouTube channels’ portrayal of snow leopard sightings on touristic trips, the article found that travel vlogs undo this elusive, difficult-to-find character of snow leopards. The vlog’s message is that it is adventurous to see the snow leopard, but the tours are comfortable, and the sighting is more or less guaranteed. In this context of the push for more tourism via vlogs, the article invites snow leopard stakeholders to acknowledge the paradox in snow leopard conservation: promoting one of the causes (tourism) of snow leopard habitat destruction in terms of tourism’s high carbon emission, as a solution to snow leopard conservation.